KINERJA DINAS PERHUBUNGAN DALAM PELAYANAN LALU LINTAS DI KABUPATEN BADUNG (STUDI KASUS: KEMACETAN LALU LINTAS DI KABUPATEN BADUNG) - Jayanti, Anak Agung Siwi Putri; Wirantari, I Dewa Ayu Putri; Supriliyani, Ni Wayan (CITIZEN CHARTER; Vol 2 No 1 (2022): Administrasi Publik 2022, 2022)
The background of this writing is based on the Regional Regulation of Badung Regency No. 18 of 2013 concerning the Implementation of Transportation by Public Motorized Vehicles related to the problem of congestion in Badung Regency caused by the imbalance of road capacity with vehicle volume. Based on this study using the theory of performance measurement of the Badung Regency Transportation Service from Agus Dwiyanto (2006) namely Productivity, Service Quality, Responsiveness, Responsibility and Accountability. This research uses a qualitative research type with a descriptive approach. The results showed that the performance of the Department of Transportation in Traffic Services in Badung Regency in minimizing traffic congestion problems was quite optimal. Recommendations that can be given in this study are to reorganize employees, provide a special base for online vehicles and disseminate information about complaints systems such as social media. Keywords: Performance, Badung Regency Transportation Service